BATU NISAN TIPE LAMURI – ‘PLANGPLENG’ GANO – LAMDINGIN - Dedy Satria (Balai Arkeologi Sumatera Utara, 2021)
Tombstone type plangpleng is a type of tombstone typology from Aceh that has not been widely known and understood, compared to the type of Acehnese tombology or 'Aceh Batu'. The shape of the tombstone and the shape of the motive form, as well as this tombstone chisel style that distinguishes it with other tombstone typologies in Aceh. Local motif themes combined with the themes of adoption from the outside then transformed well from the Hindu-Buddha-Buddha tradition and the Islamic world arts tradition combined here. This collection of tombstones was found in many places in Aceh Besar and Banda Aceh, although in limited quantities. (Simpang) Gano-Lamdingin One of the locations known to have the type of ancient tomb findings like this. The beginning of the presence of Muslim communities with Islamic government systems was reflected in the heritage of this cultural object. The kings built a tomb monument with markers of this type of tombstone. Batu nisan tipe ‘plakpleng’ merupakan satu jenis dari tipologi batu nisan dari Aceh yang belum banyak dikenal dan dipahami, bila dibandingkan jenis tipologi batu nisan Aceh atau ‘Batu Aceh’. Bentuk batu nisan dan rangcangan bentuk motif, serta gaya seni pahat batu nisan ini yang membedakannya dengan tipologi batu nisan yang lain di Aceh. Tema-tema motif lokal dipadukan dengan tema-tema adopsi dari luar lalu ditransformasikan baik yang berasal dari tradisi Hindu-Buddha Asia Selatan dan tradisi kesenian dunia Islam berpadu di sini. Kumpulan batu nisan ini ditemukan dibanyak tempat di Aceh Besar dan Banda Aceh, walau dalam jumlah terbatas. (Simpang) Gano-Lamdingin salah satu lokasi yang diketahui memiliki jenis temuan makam kuno seperti ini. Awal kehadiran masyarakat muslim dengan sistem pemerintahan Islam tercermin dari warisan benda budaya ini. Para merah atau raja-raja kecil membangun monumen makam dengan penanda dari jenis batu nisan ini.